2019
DOI: 10.1177/2045894019878615
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term results of the DelIVery for Pulmonary Arterial Hypertension trial

Abstract: BackgroundThe DelIVery for Pulmonary Arterial Hypertension clinical trial was a multi-center, prospective, single arm, Investigational Device Exemption study utilizing a fully implantable, programmable intravascular delivery system consisting of a pump and a catheter for intravenous treprostinil. The study met its primary endpoint and demonstrated that the intravascular delivery system significantly reduced catheter related complications at 22,000 subject-days of follow-up compared with a predefined objective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…Bourge et al observed a decreasing flow rate with subsequent adjustment of the dose, and noted that this was at least partly attributable to ''back pressure'' from the special catheter 10 used in their study. 11,12 In conclusion, during long-term application of intravenous treprostinil via the fully implantable LENUS Pro Õ pump, the actual flow rate differs from the distributor-specified fixed flow rate, starting below the expected rate in early months and increasing slowly but steadily above the expected rate with longer term use. Taking into account previous publications, 3,5,9 the results of this study show that the variance has the potential to cause clinically relevant events.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Bourge et al observed a decreasing flow rate with subsequent adjustment of the dose, and noted that this was at least partly attributable to ''back pressure'' from the special catheter 10 used in their study. 11,12 In conclusion, during long-term application of intravenous treprostinil via the fully implantable LENUS Pro Õ pump, the actual flow rate differs from the distributor-specified fixed flow rate, starting below the expected rate in early months and increasing slowly but steadily above the expected rate with longer term use. Taking into account previous publications, 3,5,9 the results of this study show that the variance has the potential to cause clinically relevant events.…”
mentioning
confidence: 96%
“…observed a decreasing flow rate with subsequent adjustment of the dose, and noted that this was at least partly attributable to “back pressure” from the special catheter 10 used in their study. 11,12…”
mentioning
confidence: 99%
“…Moreover, it should be kept in mind that patients with advanced PAH represent a group at highrisk for general anesthesia. Several papers have shown that the procedure may be associated with fatal complications, especially unmanageable right-sided heart failure (11)(12)(13)(14). It is therefore crucial that the procedure is performed in centers experienced in the treatment of pulmonary hypertension and that the general anesthesia is conducted by an experienced anesthetist.…”
Section: Discussionmentioning
confidence: 99%
“…The dosage can be adjusted by using various concentrations of treprostinil loaded into the pump reservoir. So far, several papers have shown that the pump implantation is relatively safe with a low risk of periprocedural complications (11)(12)(13)(14). The long-term treatment has been also shown to be safe while complications such as local infections at the site of pump implantation, catheter obstruction associated with the risk of discontinuation of treprostinil therapy, and increased pump output associated with the risk of an increased amount of applied treprostinil due to a pump failure are relatively rare.…”
Section: Introductionmentioning
confidence: 99%
“…Long-term results of the DelIVery study were recently published, further demonstrating the safety profile of the implantable system over approximately 282 patient-years. 27 Investigators recommend continued patient treatment at specialized PAH centers to preserve the risk-benefit ratio of the implantable system, until training is disseminated to other sites.
Fig 1.Overview of the Implantable System for Remodulin.
…”
Section: Introductionmentioning
confidence: 99%